Love-Based Curriculum: Fostering a Spiritual, Humanistic, and Inclusive Educational Paradigm in Madrasah - Robi'ul Afif Nurul 'Aini; Moch Solich (Tarsib: Jurnal Program Studi PGMI, 2026)
The curriculum is the foundation of the educational process that shapes learners’ character, spirituality, and social awareness. This study explores the concept and implementation of a Love-Based Curriculum (LBC) as an effort to develop a spiritual, humanistic, and inclusive paradigm in madrasah education. The main objective of this research is to examine how love centered values such as compassion, empathy, and respect for diversity can be integrated into learning design, teaching strategies, and educational culture in Islamic schools. Using a qualitative descriptive method through literature review and content analysis, this study analyzes various theoretical frameworks, educational models, and previous research related to love-based education. The findings indicate that a LBC encourages holistic learning, strengthens emotional and spiritual intelligence, and promotes inclusive attitudes among students. Moreover, it provides a moral foundation that harmonizes intellectual, emotional, and spiritual development in accordance with Islamic values. The study concludes that implementing a LBC is essential to actualize madrasah as institutions that nurture compassionate, tolerant, and morally grounded individuals.